2017
DOI: 10.4172/2329-910x.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric Exercise and Extracorporeal Shock Wave Therapy on Rehabilitation of Patients with Noncalcific Rotator Cuff Tendinopathy

Abstract: Objective: In this study, in order to establish a more effective therapeutic model for the patients with chronic rotator cuff tendinosis, the authors attempted to compare the therapeutic effects of general physical therapy, eccentric contraction exercise, extracorporeal shock wave therapy (ESWT) and their combination for patients with noncalcific subscapular tendinosis.Methods: 120 patients with subscapular tendinosis Grade II tendinopathy were divided randomly into four groups: I-IV, with 30 patients in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In research by Chen et al (25) , it was compared to conventional therapy alone to see how ESWT, eccentric exercise, and conventional therapy affected patients with non-calcific rotator cuff tendinopathy. Their findings suggested that shock wave therapy added to combination therapy produced better results and had a substantial impact on the treatment of noncalcific rotator cuff tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In research by Chen et al (25) , it was compared to conventional therapy alone to see how ESWT, eccentric exercise, and conventional therapy affected patients with non-calcific rotator cuff tendinopathy. Their findings suggested that shock wave therapy added to combination therapy produced better results and had a substantial impact on the treatment of noncalcific rotator cuff tendinopathy.…”
Section: Discussionmentioning
confidence: 99%